A Systematic Review of Usability Evaluation Approaches on Mobile Tourism Applications - Hussain, Azham; Abdulwahab Mohammed, Wasan; Isam Sabri, Manhal; Hamid Flayyih, Omar (International Journal of Engineering and Technology, 2018)
Currently, tourism faced several transformations and challenges, particularly due to the influence and due to the expansion of Information Communication Technologies (ICTs), such as Internet and smartphones. These modern technologies have significantly changed the tourists’ behavior, especially the ways of getting tourist information and travel destination. Therefore, most of the tourist enterprises adopt new competitive methods in order to improve their competitiveness and attractiveness in the tourism context. Thus, this situation opened the doors to the most recent development in the technological field, which sees mobile devices as new interesting potentials to advance the touristic sector. In fact, exploiting mobile applications in the tourist sector are useful tools, merely if well created and organized, in turn, they can damage result if they are not clearly designed. However, even though the evaluation of mobile applications is crucial and can reduce or increase of the users, little of research highlighted on the most of the approaches utilized to assess mobile tourist applications. Consequently, this paper sought to review the previous literature to explore the most methods and metrics exploited to evaluate the usability of mobile tourist applications.  The findings uncovered that, out of 27 was 88% of the selected studies used whether Questionnaire or Lab experiment as a method to evaluate the usability. While, metrics were: Comprehensibility, Effectiveness, Efficiency, Learnability, Satisfaction, Simplicity of use, Usefulness and Visualization.